RACISM, TRAUMA, AND PSYCHOLOGICAL SURVIVAL IN WARSAN SHIRE’S HOME - Bayu Purba Tendy Hidayat; Mohammad Thoyibi (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2026)
This study examines the representation of psychological trauma, systemic racism, and survival in Warsan Shire’s poem Home. Using qualitative textual analysis, the study is grounded in psychological literary criticism and trauma theory, with close reading used to identify patterns within the text. The primary data consist of the poem Home, while secondary data include relevant academic sources on trauma, racism, and migration. The findings reveal that displacement in the poem is portrayed as a condition driven by survival rather than choice. Shire represents trauma through fragmented imagery and symbolic language, reflecting the psychological instability experienced by refugees. The poem also highlights the loss of identity, where individuals are forced to renegotiate their sense of self in unfamiliar and often hostile environments. In addition, systemic racism is depicted through dehumanizing language and social hostility, which contribute to ongoing psychological distress. The study shows that trauma in Home is not only an individual experience but is closely linked to broader socio-political structures. Unlike previous studies that primarily focus on migration and identity, this study emphasizes the intersection between systemic racism and psychological trauma within poetic representations of displacement. Survival is presented as a complex process that involves both endurance and adaptation under conditions of displacement and marginalization. This study contributes to the understanding of literary representations of trauma by demonstrating how poetry can articulate the psychological and structural dimensions of refugee experiences.